Pengaruh Koneksi Politik terhadap Tax Avoidance dengan Kualitas Audit sebagai Variabel Moderasi (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The purpose of this study is to investigate the impact of political relationships on tax avoidance, with audit quality as a moderating variable. The background of this study is based on the occurrence of continuous tax avoidance methods, especially among corporations that have relationships with political entities. This study employs a quantitative approach using a causal-comparative methodology. The research sample includes manufacturing and trading companies listed on the Indonesia Stock Exchange from 2021 to 2023. Analysis utilizes multiple linear regression and MRA with a Generalized Least Squares (GLS). The findings show that political connections have a positive and significant impact on tax avoidance. However, audit quality cannot moderate this relationship. These findings suggest that companies with political connections are more likely to avoid taxes, and that external auditors have not been entirely successful in their oversight role.